Growth Response of Sea Kale (Ipomoea Pes-Caprae (L.) R. Br.) to Porong River Sediment Polluted by Lapindo Mud - Budiono, Ruly; Kusmoro, Joko; Dwiputri, Novia Amanda (International Journal of Global Operations Research, 2025)
Vegetative growth of sea kale (Ipomoea pes-caprae) can be affected by the condition of the growing medium, including sediments polluted by Lapindo mud. This study aimed to explore the effect of polluted sediments on the growth of stem cuttings of I. pes-caprae in the Porong River area. The study used an experimental approach with a completely randomized design (CRD), testing six growing media treatments: sediments of the Porong River not polluted by Lapindo mud (positive control), pure Lapindo mud (negative control), and sediments from four different locations located 0 km, 7 km, 14 km, and 21 km from the mud discharge point. Observation parameters included survival, number of shoots, shoot length, number of leaves, leaf size, root length, biomass, biomass efficiency, and root to crown ratio. Data were analyzed using one-way ANOVA with Tukey's further test at 95% confidence level. Results showed that 0 km media supported the highest growth consistently, while 7 km and 21 km media showed fluctuating results. These findings suggest that I. pes-caprae has tolerance to sediments with mild to moderate contamination, and has the potential to be used as a pioneer plant in passive revegetation and phytoremediation programs in the Porong River area affected by Lapindo mudflow.